A TRANSFORMASI DAN DIGITALISASI PENDIDIKAN DASAR DI TUBAN - Suyanto, Ahmad (Program Studi PGMI Fakultas Tarbiyah Institut Agama Islam Nahdlatul Ulama Tuban, 2023)
The purpose of this study was to describe the aspects that underwent transformation and digitization of education in Tuban District, the impact caused by the transformation and digitization of education, supporting and inhibiting factors in the transformation and digitization of education in Tuban District. While the focus of this research was on nine schools in the Tuban sub-district, namely: MI Hidayatun Najah Tuban, Kembangbilo 1 Tuban Elementary School, Sugiharjo 1 Tuban Elementary School, Sugiharjo 2 Tuban Elementary School, Bina Anak Soleh Tuban Elementary School, Insan Kamil Islamic Elementary School Tuban, Al Uswah Elementary School Tuban, SDN Doromukti Tuban, SDN Sendangharjo IV Tuban.This research is a type of qualitative research. According to Creswell, qualitative research is a form of interpretive research in which qualitative researchers make an interpretation of what is seen, heard, and understood[2]. As the name implies qualitative, in the implementation of this research it will be natural, as it is, in normal situations that are not manipulated, the circumstances and conditions emphasize natural descriptions[3]. Data collection methods used are interviews, observation, and documentation.The results of this study are data on aspects of education that have undergone the transformation of digitalization of education in the Tuban sub-district. These aspects are implementation aspects 1) e-learning 78%, 2). e-reports 73%, 3). e-administration 75%, 4). Teacher fingerprint 95%, 5). zoom meeting, google meeting 93%, 6). e-mail 63%, 7). e-books for teachers 50%, 8) School Website 83%, 9). Counseling Guidance with up-to-date technology and information 80%, 10). Computer Lab 65%. Meanwhile, 6 schools or 66.7% have experienced the transformation of digitalization of education. Meanwhile, 3 schools or 33.3% have experienced digitization transformation limited to e-reports, teacher finger print, use of e-mail, and zoom meetings which are still limited. The second result is related to the positive and negative impacts of the transformation and digitization of education in Tuban District, showing that many informants from nine schools on average stated that the existence of digitalization transformation made it easy for teachers and students to access information, learning became innovative, and fun, while the impact the negative is the tendency of teachers and students to depend on the use of gadgets, what's worse is the tendency of students to play games during class. The third result is related to the supporting factors for the transformation and digitization of education in Tuban, especially from nine school informants, on average, they stated that infrastructure such as computer labs or laptops, gadgets, internet networks or data quotas, and signals. Of the nine schools that already have computer labs, there are 6 schools or 66.7%, of which 3 or 33.3% do not yet exist. While the inhibiting factors are problems of facilities and infrastructure, data packages (data quota), signals and illiterate human resources.